2012
DOI: 10.1104/pp.112.203786
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variation in Paralogs of GDP-l-Galactose Phosphorylase Is a Major Determinant of Vitamin C Concentrations in Apple Fruit      

Abstract: To identify the genetic factors underlying the regulation of fruit vitamin C (L-ascorbic acid [AsA]) concentrations, quantitative trait loci (QTL) studies were carried out in an F1 progeny derived from a cross between the apple (Malus 3 domestica) cultivars Telamon and Braeburn over three years. QTL were identified for AsA, glutathione, total antioxidant activity in both flesh and skin tissues, and various quality traits, including flesh browning. Four regions on chromosomes 10, 11, 16, and 17 contained stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 67 publications
2
72
0
Order By: Relevance
“…GGP (VTC2) represents the first committed step of AsA biosynthesis, and has previously been suggested to be a key rate-limiting step in plants [5,9,10,43]. Recent results from our lab indicate that paralogues of apple GGP are key regulators of totAsA-AsA concentrations in fruits [10], and others have shown that ectopic expression of the single kiwifruit GGP orthologue results in enhanced totAsA contents in both transgenic tomato (3- to 6-fold increase) and strawberry (2-fold increase) [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GGP (VTC2) represents the first committed step of AsA biosynthesis, and has previously been suggested to be a key rate-limiting step in plants [5,9,10,43]. Recent results from our lab indicate that paralogues of apple GGP are key regulators of totAsA-AsA concentrations in fruits [10], and others have shown that ectopic expression of the single kiwifruit GGP orthologue results in enhanced totAsA contents in both transgenic tomato (3- to 6-fold increase) and strawberry (2-fold increase) [5].…”
Section: Discussionmentioning
confidence: 99%
“…In plants, AsA biosynthesis via the L-galactose pathway (Figure 1) as initially described by Wheeler et al [7] has been proposed to be the main route for AsA accumulation in various species [8-10], and several structural genes from this pathway have been proposed to be key regulators of fruit AsA concentrations in various species. These include GDP-L-galactose phosphorylase ( GGP, VTC2 ) in kiwifruit [9] and apple [10], and L-galactose-1-phosphate-phosphatase ( GPP, VTC4 ) [11] and GDP-mannose-3,5-epimerase ( GME ) [12] in tomato.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutants of the vtc2 gene, which encodes GGP in Arabidopsis, exhibit impaired AsA synthesis and have less abundant AsA (Linster et al 2007). GGP might be a key rate-limiting enzyme for AsA biosynthesis in Arabidopsis (Bulley et al 2009), tobacco (Laing et al 2007), and apple (Mellidou et al 2012). In previous study, SlGGP antisense transgenic tomato lines were found to maintain only 50 -75% of the ascorbate content found in WT and produced more DHA under chilling stress (Wang et al 2013).…”
Section: Discussionmentioning
confidence: 95%
“…In spite of this, QTLs for fl owering and ripening time, fruit quality, tree architecture and resistance to pathogens have been reported (Dirlewanger et al, 1996;Abbott et al, 1998;Dirlewanger et al, 1999;Etienne et al, 2002;Quilot et al 2004;Dirlewanger et al, 2006;Lambert et al, 2007;Ogundiwin et al, 2008;Dirlewanger et al, 2009 (Zini et al, 2005;Dunemann et al, 2009;Dunemann et al, 2012;Khan et al, 2012;Chagne et al, 2012b;Vogt et al, 2013;, texture (King et al, 2000;King et al, 2001;Kenis et al, 2008;Costa et al, 2008;Costa et al, 2010;Longhi et al, 2012;Longhi et al, 2013), ethylene production (Costa et al, 2014), Vitamin C content (Davey et al, 2006;Mellidou et al, 2012;) and fl esh browning (Kenis et al, 2008;Di Guardo et al, 2013). Also, as the cost of map construction was higher, the eff orts were concentrated in a few mapping populations and often they were considered as reference progenies, but these populations only segregated for a few traits.…”
Section: How To Transform a Polymorphism Into A Selection Marker?mentioning
confidence: 99%